ANALISIS UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA DITINJAU DARI PERSPEKTIF HAK ASASI PEREMPUAN DALAM UPAYA MEWUJUDKAN ACCSESS TO JUSTICE BAGI PEREMPUAN KORBAN KEKERASAN - Atikah, Gita Ayu; Riwanto, Agus (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2020)
Every person has human rights which are inherent to them from birth, one of the human rights is violence prevention, it is compulsory for all citizens by The Indonesian State Ideology (Pancasila) and The 1945 Constitutions of the Republic of Indonesia (Undang – Undang Dasar Republik Indonesia Tahun 1945) “All types of violence, especially violence against women and domestic violence break the human rights and develop into crime against human dignity and discrimination which come to an end.” Hierarchy of the human rights’ principle places public human rights violations at a higher position which is more important and gets priority than domestic human rights violations, it is not even considered as the human rights abuses. This hierarchy makes the domestic violence is neglected and beyond the reach of the law. This is a legal research and the research uses statute approach, conceptual approach, and historical approach. The legal materials of the research are primary legal materials and secondary legal materials. The research uses the technique of literature study to collect the legal materials and the technique of deductive analysis with syllogism method to analyze the legal materials. The understanding of domestic violence (Kekerasan dalam Rumah Tangga or KDRT) continues varying which causes the implementation of Domestic Violence Act 23, 2004 in maintenance of law, civil society support, and public administration and therefore tend to harm victims’ rights in handling domestic violence. As the result, it requires arranging a national action scheme for ending domestic violence; it should make the efforts to achieve the Access to Justice. First, it requires progressive legal service foundation for procurement and dispute. Second, it requires legal aid foundation to give training and education for vulnerable groups. Third, it requires adequate infrastructures for accessing the justice. Fourth, it requires strong complaint and supervision institutions to protection, honor and fulfillment for vulnerable groups. The legal development based on justice is a medium to protection, honor and fulfillment for the rights of vulnerable groups when they deal with problems by government’s agenda and arbitrariness industrial system.